2005
DOI: 10.1677/joe.1.05983
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor expression and in vitro leptin actions on prostaglandin release and nitric oxide synthase activity in the rabbit oviduct

Abstract: In this study, we have examined the presence and the distribution of receptors for leptin (Ob-R) in the oviduct of rabbits, and the effects of leptin on the release of prostaglandin (PG) F2 and PGE2 and on the activity of nitric oxide (NO) synthase (NOS) by oviducts cultured in vitro. Rabbits were killed during the follicular phase and the oviducts were incubated in vitro with leptin, PGF2 , PGE2, NO donor and inhibitors of NOS and cyclooxigenase (COX). Using immunohistochemistry, Ob-Rlike positive reaction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Moreover, so far there were no reports on the detection of leptin receptor in the oviductal tissue in birds. ZERANI et al (2005) detected positive immunohistochemical staining of leptin receptor in the cytoplasm of the secretory cells of the rabbit oviduct.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, so far there were no reports on the detection of leptin receptor in the oviductal tissue in birds. ZERANI et al (2005) detected positive immunohistochemical staining of leptin receptor in the cytoplasm of the secretory cells of the rabbit oviduct.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, the present study is the first concerning mRNA expression of both long and short isoform of leptin receptor in the chicken oviduct. Previously, in mammalian oviduct, mRNA expression of long form of leptin receptor was detected (LIU et al 2003;ZERANI et al 2005), but there were no data on other isoforms of leptin receptor. Moreover, so far there were no reports on the detection of leptin receptor in the oviductal tissue in birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been relatively few data to date that elucidate the effect of leptin and its receptor on human endometrial cancer, and no further studies concerning leptin and COX‐2 expression and function. Leptin has been reported to increase PGF2α but inhibit PGE2 production ( 51 ) in the rabbit oviduct, while leptin has been shown to increase COX‐2 expression and PGE2 release in murine macrophage J774A.1 cells. ( 52 ) In this study, we showed that leptin stimulates COX‐2 activation dose‐ and time‐dependently which derived from leptin‐mediated COX‐2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian function mechanism is also dependent on leptin, a hormone produced in adipose tissue. The presence of leptin receptors on ovaries (101) and in the fallopian tubes (100) has been demonstrated in rabbits. The presence of receptors for leptin suggests its importance in the formation of preovulatory follicles and for the survival of oocyte and subsequently the blastocyst in the fallopian tube.…”
Section: Maternal Cyclical Phenomenamentioning
confidence: 99%